Growth, water resilience, and sustainability: A DSGE model applied to South Africa - Chuan-Zhong Li; Ranjula Bali Swain (Uppsala University, Department of Economics, 2014)
In this paper, we analyze a dynamic stochastic general equilibrium model on how water resilience affacts economic growth and dynamic welfare with special reference to South Africa. While water may become a limiting factor for future development in general, as a drought prone and water poor country with rapid population growth, South Africa may face more serious challenges for sustainable development in the future. Using the model, we conduct numerical simulation for different parameter configurations with varying discount rate, climate change assumption, and the degree of uncertainty in future precipitation. We find that with sufficient capital accumulation, development can still be made sustainable despite of increased future water scarcity and decreased long-run sustainable welfare; While stochastic variation in precipitation has a negatively effect on water resilience and the expected dynamic welfare, the effect is mitigated by persistence in the precipitation pattern. With heavier time discounting and lower capital formation, however, the current welfare may not be sustained.
urn:nbn:se:uu:diva-239182
Keywords: O4; D6; Q25; O55; 330; water resilience; growth; dynamic welfare; sustainability